EVALUASI KEBIJAKAN KETENAGAKERJAAN DALAM PERSPEKTIF PENJAMINAN HAK DAN KESEJAHTERAAN PEKERJA PERUSAHAAN GARMEN PT X DI KABUPATEN JEPARA PADA TAHUN 2023 – 2024 - Nawal Sabil Muzakki; Lusia Astrika (Journal of Politic and Government Studies, 2026)
Employment is one of the fundamental pillars of national development because it directly affects economic stability, public welfare, and the quality of social life. In the context of an increasingly competitive labor market dynamic, issues such as worker rights protection, industrial relations, and the evaluation of effective employment policies are becoming increasingly crucial to address. These challenges are further complicated by structural changes, such as digitalization, globalization, and the shift in corporate orientation toward efficiency and labor flexibility. This study aims to evaluate employment policies at the garment company PT X in Jepara Regency and assess the extent to which national regulations and company policies are able to ensure the protection of workers’ rights and welfare. Using a descriptive qualitative method based on James Anderson’s theory of systematic policy evaluation through in-depth interviews, observations, and document analysis, this study provides an empirical description of the implementation of workers’ rights in the context of the manufacturing industry. The study shows that the company has fulfilled several normative obligations such as paying wages according to the regional minimum wage (UMK), registering workers in social security programs (BPJS), providing safety equipment, and recognizing labor unions. However, these fulfillments remain administrative in nature and are not yet oriented toward substantive welfare. Wages do not yet reflect a decent standard of living, the occupational safety and health culture remains weak, leave rights are rarely used due to production pressure, and labor unions are not fully independent. The study emphasizes the existence of a gap between regulatory norms and implementation realities in the field. This research contributes by showing that the main problem does not lie in the regulations but in weak supervision and unequal power relations. The practical implications underline the need for strengthening substantive supervision, increasing the capacity of labor unions, and improving company policies to realize fair industrial relations.